Development of impact test device - Mohd Naqiuddin, Mohd Salleh (2009)
The objective of this project is to design and fabricate impact test device for ITS model. In Panasonic not have the suitable tester for impact test, so this project to make specific device test. This tester for KX-TS500 only with can adjust the height and width and the load of impact test is depends the weight of steel ball 1kg or equivalent. Before fabricate the impact test, on researches about drilling and welding. To get the suitable concept must have another concept and choose the best concept with some criteria. Finally, the best concept as a final concept. Choose the suitable material with have long life time. It have many work to fabricate the product such as measuring, cutting, drilling, and finally is painting to avoid the product become corrosion. To running this tester must have the procedure to avoid any accident. The purpose of this project is to know the condition of surface. If the surface is crack, so the strength of surface is not enoughly to produce the model.